Cultural competence now : 56 exercises to help educators understand and challenge bias, racism, and privilege - Mayfield, Vernita (ASCD, 2020)
"What will it take to create equitable educational opportunities for all students? According to veteran educator Vernita Mayfield, teachers and school leaders need to learn how to recognize culturally embedded narratives about racial hierarchy and dismantle the systems of privilege and the institutions that perpetuate them with knowledge, action, and advocacy. Cultural Competence Now provides a structure to begin meaningful conversations about race, culture, bias, privilege, and power within the time constraints of an ordinary school. The 56 exercises include activities, discussions, and readings in which to engage during each of the four quarters of the school year. School leaders will discover how to facilitate learning through the four steps--awaken and assess; apply and act; analyze and align; advocate and lead--as you and your colleagues * Increase your awareness of privilege and bias. * Adapt your professional practices to meet the needs of all students. * Examine policies and practices that inhibit opportunities for marginalized populations. * Align resources to eradicate inequity in your school. Mayfield offers advice on establishing a safe environment for professional conversations, setting goals for cultural competency, overcoming resistance, reviewing school data and the school's vision and mission through the lens of race and culture, and strategically managing what can be a transformative yet uncomfortable change process. Cultural Competence Now responds to the urgent need to build the cultural competency of educators--for the sake of children and in the interest of supporting and retaining all educators."--